Intuitive eating, objective weight status and physical indicators of health - N. G. Keirns; M. A. W. Hawkins (Wiley, 2019)
Summary Introduction Intuitive eating (IE) has emerged as a weight‐neutral approach to health promotion for those with overweight/obesity. This weight‐neutral paradigm has some support, although research thus far has often neglected to control for potential confounds (i.e. objective weight status and demographics) and foundational studies are lacking. The objective of the current study was to observe the unique association of IE with physical health indicators in a sample of adults, independent of objective weight status. Methods Participants were 248 adults (32 ± 14 years old, 73% female, 64% White) of all weight categories (18.2-55.3 kg m−2), with an average body mass index (BMI) of 30 ± 8 kg m−2. IE was measured with the Intuitive Eating Scale‐2 (IES‐2). BMI was objectively measured in‐lab. Health indicators included blood pressure (BP) and fasting glucose. Results A series of hierarchical linear regressions revealed no significant associations between IE and systolic BP (β = −0.076, P = 0.256), diastolic BP (DBP; β = −0.122, P = 0.073) or fasting glucose (β = 0.047, P = 0.500) after controlling for BMI. All effects sizes were small or below (f2 = 0.00 to −0.04). Sensitivity analyses revealed significantly lower DBP in high intuitive eaters versus low when analysed with a t‐test, t(111.651) = 3.602, P < 0.001, Levene corrected; however, after controlling for relevant covariates (i.e. BMI and demographics), analysis of covariance revealed no difference in DBP between groups, F(1, 116) = 0.330, P = 0.567. No significant differences in systolic BP or fasting glucose were observed between low and high intuitive eaters before or after considering covariates. Conclusions In sum, this study investigated associations between IE and common indicators of physical health after controlling for objective weight status. Findings revealed no unique relationship between IE and physical health, and any IE-physical health relationships that were observed were accounted for BMI and/or demographic factors.